Personalized Nutrition Education to the Adherence to Dietary and Physical Activity Recommendations - González Rodríguez, Liliana Guadalupe; Perea Sánchez, José Miguel; Veiga Herreros, Pablo Jesús; Peral Suárez, África (My University, 2019)
In recent years, there has been a significant increase worldwide in the prevalence and incidence of noncommunicable diseases both in children and adults. There is a strong relationship between lifestyle and health, and unhealthy dietary patterns, limited physical activity, and harmful alcohol and tobacco consumption are strongly associated with risk of disease and death. Most of the population does not meet the national dietary and physical activity recommendations. Food choice is a complex process that is influenced by different determinants that must be taken into account in the design of a nutrition education intervention. Traditional nutrition education approach has been considered ineffective, therefore there is a need to design and apply new models to support people to adhere to the dietary and physical guidelines. Personalized nutrition education plays a key role in the promotion of healthy eating habits, active lifestyle, and related health behaviors. However, it should be based on scientific evidence, by identifying the factors that determine dietary behavior change at the individual, family, and community levels and using the appropriate behavior change strategies. The development of nutritional education intervention needs planning, which begins with the knowledge of the nutritional situation of the individual in order to establish the diagnosis of the situation and to be able to intervene effectively. The Nutrition Education DESIGN procedure is a systematic stepwise behaviorally-focused and theory-based process to design effective strategies for personalized nutrition education. This procedure consists of defining the specific behavior goal, exploring the determinants of change, selecting appropriate theories to establish an adequate action plan, motivating individual and translate intentions into action. It aims to set general objectives in consensus with the individual, generate the action plan, and design the evaluation of the intervention.